(untitled) (Texas Journal of Multidisciplinary Studies, 2026)
The psychological state of an employee is of great importance in the work process. Factors such as occupational stress, physical and mental fatigue, and work monotony, that is, boredom, may negatively affect an employee’s health and productivity. These conditions can be observed in various fields - from transport to manufacturing and healthcare, from military service to office and educational environments. In order to take effective measures against them, it is first necessary to know the methods of identifying and measuring these conditions, and then to apply appropriate management strategies